Evaluation of targetron based mutagenesis in Ehrlichia chaffeensis - Gong, Shanzhong (Kansas State University, 2010)
Ehrlichia chaffeensis is an emerging tick-borne rickettsial pathogen that causes infection in people and several vertebrate animals. One of the striking features of E. chaffeensis infection is the prolonged persistence in its vertebrate and tick hosts. The mechanism of persistent infection and the reasons for the host immune system failure to clear the infection are not well understood. One hypothesis is that differential gene expression serves as an important adaptive mechanism used by E. chaffeensis in support of its continued survival in both tick and vertebrate hosts. One way to test this hypothesis is by performing mutational analysis. However, the methods for introducing mutations in this pathogen have not yet been documented and are challenging, possibly due to its obligate, intraphagosomal growth requirement. Recently, a novel gene mutation method called ‘TargeTron Gene Knockout System’ that is based on the modified group II intron insertion strategy has been developed. This method appears to be effective in creating mutations in a wide range of gram positive and gram negative bacterial organisms. The group II intron can be programmed for insertion into virtually any desired DNA target with possibly high frequency and specificity. In this study, I focus on creating mutations in E. chaffeensis using the TargeTron gene knockout system. I prepared modified group II intron constructs retargeting for insertion into three E. chaffeensis genes: Ech_0126 (a transcriptionally silent gene), macrophage-specific expressed gene (p28-Omp 19, Ech_1143) and tick cell-specific expressed gene (p28-Omp 14, Ech_1136). In support of driving the expression of the modified group II introns in E. chaffeensis, the pathogen- specific high-expressing gene promoter (tuf) was inserted upstream to the transcription start site. In addition, a chloramphenicol acetyltransferase gene with E. chaffeensis rpsl promoter was introduced for use as a selection marker. The constructs were then evaluated by transforming into E. chaffeensis. Transformants with mutations, introduced in two of the three genes (Ech_0126 and Ech_1143), were identified by PCR and Southern blot methods. Although the mutants are detectable for up to 48 hours, establishment of stable transformants remains to be challenging. The outcomes of this project will have important implications in defining the pathogenesis of E. chaffeensis, particularly to assess the differences in the organism in tick and vertebrate hosts.
Keywords: Ehrlichia chaffeensis; Targetron; Agriculture, Animal Pathology (0476); Biology, Microbiology (0410); Biology, Molecular (0307)